Pengaturan Hukum Penggunaan Detektor Kebohongan (Lie Detector/ Polygraph) dalam Proses Hukum Acara Pidana: Penelitian - I Made Deni Dwi Nuarthawan; Made Sugi Hartono (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The use of lie detectors (polygraphs) in Indonesia’s criminal procedure raises juridical issues, as such devices are not explicitly recognized as valid evidence under Article 184 paragraph (1) of the Criminal Procedure Code (KUHAP). Although theoretically, the polygraph can be classified as electronic information pursuant to Article 5 of Law No. 11 of 2008 on Electronic Information and Transactions (ITE Law), its application encounters normative obstacles, particularly the vagueness of Article 13 paragraph (2) letter d of the National Police Regulation No. 10 of 2009, which requires that the subject be “not under pressure” without providing objective indicators. This normative ambiguity potentially violates constitutional rights of suspects, including the principles of non self-incrimination and due process of law. This research employs a normative juridical method with statute, conceptual, and case approaches. The analysis is conducted qualitatively in an analytical-prescriptive manner by examining the Denpasar District Court Decision No. 708/Pid.B/2015 and the East Jakarta District Court Decision No. 229/Pid.Sus/2014. The findings indicate that the lie detector cannot yet serve as an independent means of evidence due to the absence of a clear legal basis and its potential to infringe human rights. Therefore, legal reform is necessary through revising the Police Regulation, improving Supreme Court Regulations (PERMA), and introducing new provisions in the revised KUHAP and ITE Law to establish a comprehensive legal framework that ensures the protection of rights within the criminal justice process.